(untitled) (Conference Series, 2022)
This abstract presents an overview of a study focused on quantitative research, addressing research problems and ethical considerations. The study aims to provide direct answers to research questions through the formulation of hypotheses and research statements. It emphasizes the importance of expressing gratitude to those who contribute to scientific research, including funding providers, facilities supporters, and collaborators. Ethical standards are highlighted, with a focus on avoiding plagiarism, practicing effective quoting skills, and adhering to principles such as non-maleficence, beneficence, justice, respect for individuals, and informed consent. The study highlights the significance of formulating research problems and concludes that narrative conclusions should directly address the research question(s). Overall, the study emphasizes the importance of ethical conduct, acknowledges the support received in scientific research, and emphasizes the need for clear and direct conclusions.